IDENTIFIKASI SERANGGA HAMA DAN TINGKAT KERUSAKAN BIBIT TREMBESI (Samanea saman (Jacq.). Merr. DI AREAL BPDASHL KAPUAS KOTA PONTIANAK - Koteng, .; Suryantini, Rosa; Herawatiningsih, Ratna (Universitas Tanjungpura, 2019)
Trembesi is a fast growing species and has a high resistance to the environment and can be harvested within a short period of planting rotation of 5-8 years. This type was chosen because it has a unique texture, besides that this tree is believed to be able to contribute to tackling air pollution and the threat of global warming. Trembesi is also a tree that is an alternative that can be cultivated extensively for the purpose of rehabilitating marginal lands. However, the supply of healthy and quality trembesi seeds is still constrained by the presence of destructive pest insects. This study aims to identify pest insects that attack trembesi seedlings and determine the level of damage caused by pest insects by using calculations based on the types of visible damage, in the permanent nursery area of Kapuas City of Pontianak. The method used in this study is the census method with direct observation of trembesi seeds in the nursery. The results of the study stated that there were 5 types of insects which were thought to attack trembesi seeds, in the nursery area there were 5 types which included cone grasshopper (Tagasta marginella), Small grasshopper (Oxya sp.), Woodhopper (Valanga nigricornis). the Hemiptera order includes the walang sangit (Leptocorisa acuta). caterpillar tritip (Plutella sp.), The results showed an average percentage of damage caused by insect pests was 34.02% and the percentage level of damage was 22,02% of the total seedlings of 2,880 seeds observed and included in the category of minor damage. Although including the category of minor damage, it is necessary to further improve cleaning in the environment around the nursery area so that it can reduce the potential percentage and damage to the seedlings.Keywords: Identification, insects, level of destruction, pests, trembesi seedlings